2016
DOI: 10.5762/kais.2016.17.12.292
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Case-Based Learning using video In Emergency care of infant and toddlers

Abstract: The purpose of this study was to investigate the effects of case-based learning about infants and toddlers on healthcare department students, using a video in an emergency care environment. A total of 57 students from a healthcare department of D university in J city were enrolled. They were divided into two groups: The experimental group (n=29) and the control group (n=28). This study is pre-post designed with a non-equivalent control group. The experimental group received a 1-week education for a duration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
2
1
0
Order By: Relevance
“…The analysis of pretest-posttest differences for self-efficacy in coping with emergencies between the two groups revealed significantly higher scores in the EG. This finding is in line with the results of previous studies that have applied case-based small-group learning [45,47,48]. In South Korea, care workers are most often the first emergency responders for LTCS recipients, which denotes that self-efficacy in coping with emergencies is a necessary skill for these professionals.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The analysis of pretest-posttest differences for self-efficacy in coping with emergencies between the two groups revealed significantly higher scores in the EG. This finding is in line with the results of previous studies that have applied case-based small-group learning [45,47,48]. In South Korea, care workers are most often the first emergency responders for LTCS recipients, which denotes that self-efficacy in coping with emergencies is a necessary skill for these professionals.…”
Section: Discussionsupporting
confidence: 89%
“…These results align with those of Prickett et al's study, which conducted an emergency tracheostomy education intervention for care workers; at posttest, care workers' confidence in performance showed an increase [44]. Other studies that applied CBL have also observed an increase in the levels of practice performance [39,45,46], and the results support these earlier findings.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation